Characteristics and outcomes of neonates with intrapartum asphyxia managed with therapeutic hypothermia in a public tertiary hospital in South Africa - Firdose Lambey Nakwa; Letlhogonolo Sepeng; Alison van Kwawegen; Reenu Thomas; Karabo Seake; Tshiamo Mogajane; Nandi Ntuli; Claude Ondongo-Ezhet; Samantha Kesting; Dikeledi Maureen Kgwadi; Noela Holo Bertha Kamanga; Annaleen Coetser; et al. (BMC, 2023)
Abstract Background In randomized clinical trials, therapeutic hypothermia (TH) has been shown to reduce death and/or moderate-to-severe disability in neonates with hypoxic ischemic encephalopathy (HIE) in high-income countries, while this has not consistently been the case in low-and middle-income countries (LMICs). Many studies reporting on outcomes of neonates with HIE managed with TH are those conducted under controlled study conditions, and few reporting in settings where this intervention is offered as part of standard of care, especially from LMICs. In this study we report on short-term outcomes of neonates with moderate-to-severe HIE where TH was offered as part of standard of care. Objective To determine characteristics and mortality rate at hospital discharge in neonates with moderate-to-severe HIE. Methods Hospital records of neonates with intrapartum asphyxia were reviewed for clinical findings, management with TH (cooled or non-cooled) and mortality at hospital discharge. Inclusion criteria were birthweight ≥ 1800 g, gestational age ≥ 36 weeks and moderate-to-severe HIE. Comparisons were made between survivors and non-survivors in cooled and/or non-cooled neonates. Results Intrapartum asphyxia was diagnosed in 856 neonates, with three having no recorded HIE status; 30% (258/853) had mild HIE, and 595/853 (69%) with moderate-to-severe HIE. The overall incidence of intrapartum asphyxia was 8.8/1000 live births. Of the 595 with moderate-to-severe HIE, three had no records on cooling and 67% (399/592) were cooled. Amongst 193 non-cooled neonates, 126 (67%) had documented reasons for not being cooled with common reasons being a moribund neonate (54.0%), equipment unavailability (11.1%), pulmonary hypertension (9.5%), postnatal age > 6 h on admission (8.7%), and improvement in severity of encephalopathy (8.7%). Overall mortality was 29.0%, being 17.0% and 53.4% in cooled and non-cooled infants respectively. On multivariate analysis, the only factor associated with mortality was severe encephalopathy. Conclusion Overall mortality in neonates with moderate-to-severe HIE was 29.0% and 17.0% in those who were cooled. Cooling was not offered to all neonates mainly because of severe clinical illness, equipment unavailability and delayed presentation, making it difficult to assess overall impact of this intervention. Prospective clinical studies need to be conducted in LMIC to further assess effect of TH in short and long-term outcomes.